PENGARUH PENERAPAN STANDAR OPERASIONAL PROSEDUR DAN KOMPETENSI TERHADAP PRODUKTIVITAS KERJA KARYAWAN DIVISI EKSPOR PT. DUA KUDA INDONESIA - Pratama, Satria Artha; Permatasari, Rita Intan (Feb Universitas Dirgantara Marsekal Suryadarma, 2021)
PT Dua Kuda Indonesia is a company engaged in chemical manufacturing. The main problem is the stages of filling out the Export Declaration of Goods that are not in accordance with Standard Operating Procedures and the lack of employee background for marine transportation management graduates causing obstruction in filling out the Export Declaration of Goods so that productivity does not reach the target. This study aims to examine the effect of the application of standard operating procedures and competence on Work Productivity of PT Dua Kuda Indonesia Export Division Employees. This study uses a quantitative approach. The population in this study were all employees of the Export Division as many as 32 employees. The technique used is saturated sampling. Data collection techniques in this study used statistical tools similar to SPSS version 21. Based on the results of data processing, a regression equation was obtained which illustrates a positive effect between Standard Operating Procedures and Work Productivity, a positive effect between Competence and Work Productivity. Simultaneously, Standard Operating Procedures and Competencies have an effect on Employee Work Productivity. The coefficient of determination (R2) shows that the variant of the independent variable is able to explain the dependent variable by 62,8%, while the remaining 37,2% can be explained by other factors that are not discussed in this study.Keywords: standard operating procedure, competence, work productivity